IMPLEMENTATION OF SEPIC IN SMALL SCALE WIND POWER GENERATION SYSTEM - Alsumiri, Mohammed; Althomali, Raed (MATTER: International Journal of Science and Technology, 2017)
Wind power generation system in a small scale application considered as one of the cost effective solutions since the energy price increases. Also, it can be an alternative solution for people who live in rural areas, where they do not have access to the national grid. This research investigate the implementation of a Single-Ended Primary-Inductor Converter (SEPIC) in a Permanent Magnet Synchronous Generator (PMSG) based Wind Power Generation System (WPGS).Variable structure control has been employed to compensate the uncertainties in WPGS and to improve the energy conversion efficiency. This paper illustrates the dynamic model of the PMSG and the controller design. A simplified controller design based on an improved sliding surface has been presented. Maximum Power Point Tracking (MPPT) algorithm has been followed to harvest maximum energy from the wind. The results show satisfactory dynamic performance of the WPGS and maximum power coefficient has been achieved.